'Intracytoplasmic sperm injection (ICSI) paradox' and 'andrological ignorance': AI in the era of fourth industrial revolution to navigate the blind spots - Sengupta, Pallav; Dutta, Sulagna; Jegasothy, Ravindran; Slama, Petr; Cho, Chak-Lam; Roychoudhury, Shubhadeep (Reproductive biology and endocrinology, 2024)
The quandary known as the Intracytoplasmic Sperm Injection (ICSI) paradox is found at the juncture of Assisted Reproductive Technology (ART) and 'andrological ignorance' - a term coined to denote the undervalued treatment and comprehension of male infertility. The prevalent use of ICSI as a solution for severe male infertility, despite its potential to propagate genetically defective sperm, consequently posing a threat to progeny health, illuminates this paradox. We posit that the meteoric rise in Industrial Revolution 4.0 (IR 4.0) and Artificial Intelligence (AI) technologies holds the potential for a transformative shift in addressing male infertility, specifically by mitigating the limitations engendered by 'andrological ignorance.' We advocate for the urgent need to transcend andrological ignorance, envisaging AI as a cornerstone in the precise diagnosis and treatment of the root causes of male infertility. This approach also incorporates the identification of potential genetic defects in descendants, the establishment of knowledge platforms dedicated to male reproductive health, and the optimization of therapeutic outcomes. Our hypothesis suggests that the assimilation of AI could streamline ICSI implementation, leading to an overall enhancement in the realm of male fertility treatments. However, it is essential to conduct further investigations to substantiate the efficacy of AI applications in a clinical setting. This article emphasizes the significance of harnessing AI technologies to optimize patient outcomes in the fast-paced domain of reproductive medicine, thereby fostering the well-being of upcoming generations.
Keywords: Sperm Injections, Intracytoplasmic; intracytoplazmatické injekce spermie; Reproductive Techniques, Assisted; Male infertility; Intracytoplasmic sperm injection; Semen; Andrology; lidé; umělá inteligence; sperma; asistovaná reprodukce; Infertility, Male; Artificial intelligence; Male; Industrial revolution 4.0; Assisted reproductive technology; mužské pohlaví; mužská infertilita; Artificial Intelligence; Humans